Evaluation of neutrophil CD64 in neonatal sepsis - Dhlamini, Matshediso Bernice (My University, 2012)
Neonatal sepsis remains a global health problem due to its significant contribution to morbidity and mortality. The blood culture is the most reliable method for detection of bacterial infections. However, the sensitivity of the latter method is low and using it as a gold standard in diagnosis of bacteremia is fraught with difficulties. Neutrophil CD64 levels are upregulated in response to inflammation and tissue injury. We quantitated neutrophil CD64 by flow cytometry in neonates with signs and symptoms suggestive of sepsis/infection within the 1st four weeks of life in a prospective observational study conducted at 3 hospitals in Johannesburg. Patients were classified into categories of infection namely definite, probable and possible according to signs and symptoms of infection and blood tests including blood culture results. Of 76 neonates, there was 1 infant with definite infection, 5 infants with probable, 30 infants with possible and 32 infants with no infection. The PMN CD64 at cut off of 1.8 had a high negative predictive value in ruling out definite (100%) or probable + definite infection (95.2%). We recommend the inclusion of PMN CD64 index into the diagnostic algorithm for neonatal sepsis, as it has a high negative predictive value and can be used to rule out infection. As the positive predictive value of the test was low in confirming infection, PMN CD64 should be used as a screening rather than confirmatory test.
Keywords: Infant, Newborn, Diseases; Sepsis--therapy